Yahoo Web Search

  1. Sort by

  1. r/5 + 6/5 = r/7 + 8/7 7r + 42 = 5r + 40 2r = - 2 r = - 1 Answer: r = - 1 Checking: - 1/5 + 6/5 = - 1/7 + 8/7 5/5 = 7/7 1 = 1

    2 Answers · Science & Mathematics · 17/11/2010

  2. R(x) = -2x³ - 7x + 14 R(11) = -2(11)³ - 7(11) + 14 R(11) = -2(1331) - 77 + 14 R(11) = -2662 - 77 + 14 R(11) = -2725

    3 Answers · Science & Mathematics · 03/07/2008

  3. I = e/R + r IR = e + rR {multiply both sides by R} IR - rR = e {subtract rR from both sides} (I - r)R = e {factor left side} R = e/(I - r) {divide both sidea by (I - r)

    4 Answers · Science & Mathematics · 13/10/2007

  4. f(r) = |(r - 2)(r - 1)|. As a piecewise defined function f(r) = (r - 2)(r - 1) if r ≤ 1 or r ≥ 2 f(r) = -(r - 2... that f ' isn't defined at r = 1. f has three critical values on the...

    1 Answers · Science & Mathematics · 27/06/2013

  5. lim ((a^r + b^r)/2)^(1/r) (as r --> 0) LN lim = lim LN lim LN ((a^r + b^r)/2)^(1/r) = = lim (1/r)LN ((a^r + b^r)/2) (as r --> 0) is...

    3 Answers · Science & Mathematics · 15/10/2012

  6. Complete the square r^2 + 3r = 2 (r + 3/2)^2 - 9/4 = 2 (r + 3/2)^2 = 2 + 9/4 (r + 3/2)^2 = 17/4 r + 3/2 = +/- Sqrt 17/4 r = - 3/2 +/- Sqrt 17/4 If you need to go further r = - 3/2 + 2.0615 = 0.5615 r = - 3/2 - 2.0615 = - 3.5615

    1 Answers · Science & Mathematics · 16/08/2010

  7. ✰Answer✰ r = (-3y - 2k)/(a - 1) ✐Derivation✐ 2k + ar = r - 3y Try different... is the better way to solve for r. ar = r - 3y - 2k ar - r = -3y - 2k Factor the left side. r(a - 1) = -3y - 2k r = (-3y - 2k)/(a...

    3 Answers · Science & Mathematics · 27/07/2012

  8. GL(n,R) is the group of nxn invertible matrices under matrix multiplication, and... with determinant 1. Now first we have to show that SL(2,R) is a subgroup of GL(2,R). Clearly the identity element...

    1 Answers · Science & Mathematics · 06/04/2012

  9. I use DVD+R but it depends on your DVD burner. Most older...1) The DVD-R (pronounced "DVD dash R") and -RW media formats are officially approved...

    5 Answers · Consumer Electronics · 26/12/2006

  10. (r^(2)-36)/((r+6)^(2)) The binomial can be factored using the difference...difference of squares formula is a^(2)-b^(2)=(a-b)(a+b). ((r-6)(r+6))/((r+6)^(2)) Reduce the expression by canceling out...

    5 Answers · Science & Mathematics · 06/03/2010

  1. Try asking your question on Yahoo Answers